(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The hospital is a universal method by which any patient can undergo medical examinations, diagnose diseases and get recommendations for any type of treatment. Most people all over the world follow this custom. People have considered this to be the most suitable and authentic way to keep a check on their physical body state. The proposed system is to find another alternative to this formal way of having to visit a hospital and to make an appointment for a check-up or diagnosis with a doctor. This particular research study will help to apply the concepts of natural language processing and machine learning to create a chatbot application. Just like people interact with each other, here people can easily interact with the chatbot through a series of questions and doubts, meanwhile the chatbot will find and identify the person’s symptoms and thereby can predict which disease the person is affected with and suggest the related remedies and treatment. This system can be proved to be of great use especially to people who have to conduct diurnal check- ups, It can also enable people to understand their health and encourage more people to take appropriate measures to maintain their health. This research also suggests that such a system is not very popularly used and people lack knowledge about this. Putting into action this framework can be of great help to people in avoiding long-distance trips to the hospital just by using this free app no matter where you are.